Infinitely Many Solutions for a Boundary Value Problem with Discontinuous Nonlinearities. (23rd February 2009) - Bonanno, Gabriele; Bisci, Giovanni Molica
Abstract : The existence of infinitely many solutions for a Sturm-Liouville boundary value problem, under an appropriate oscillating behavior of the possibly discontinuous nonlinear term, is obtained. Several special cases and consequences are pointed out and some examples are presented. The technical approach is mainly based on a result of infinitely many critical points for locally Lipschitz functions.